A Bird's Eye View of Civilians Killed by Police in 2015: Further Evidence of Implicit Bias. Issue 1 (8th February 2017) - Nix, Justin; Campbell, Bradley A.; Byers, Edward H.; Alpert, Geoffrey P.
Abstract : Research Summary: We analyzed 990 police fatal shootings using data compiled by The Washington Post in 2015. After first providing a basic descriptive analysis of these shootings, we then examined the data for evidence of implicit bias by using multivariate regression models that predict two indicators of threat perception failure: (1) whether the civilian was not attacking the officer(s) or other civilians just before being fatally shot and (2) whether the civilian was unarmed when fatally shot. The results indicated civilians from "other" minority groups were significantly more likely than Whites to have not been attacking the officer(s) or other civilians and that Black civilians were more than twice as likely as White civilians to have been unarmed. Policy Implications: We implore the U.S. government to move forward with its publication of a national police use‐of‐force database, including as much information about the officers involved as possible. We further suggest police departments use training programs and community activities to minimize implicit bias among their officers.